Enhanced foliar 15 N enrichment with increasing nitrogen addition rates: Role of plant species and nitrogen compounds - Yinliu Wang; Guoxiang Niu; Ruzhen Wang; Kathrin Rousk; Ang Li; Muqier Hasi; Changhui Wang; Jianguo Xue; Guojiao Yang; Xiaotao Lü; Yong Jiang; Xingguo Han; et al. (Global Change Biology, 2023)
Determining the abundance of N isotope (δ 15 N) in natural environments is a simple but powerful method for providing integrated information on the N cycling dynamics and status in an ecosystem under exogenous N inputs. However, whether the input of different N compounds could differently impact plant growth and their 15 N signatures remains unclear. Here, the response of 15 N signatures and growth of three dominant plants ( Leymus chinensis , Carex duriuscula , and Thermopsis lanceolata ) to the addition of three N compounds (NH 4 HCO 3 , urea, and NH 4 NO 3 ) at multiple N addition rates were assessed in a meadow steppe in Inner Mongolia. The three plants showed different initial foliar δ 15 N values because of differences in their N acquisition strategies. Particularly, T. lanceolata (N 2 ‐fixing species) showed significantly lower 15 N signatures than L. chinensis (associated with arbuscular mycorrhizal fungi [AMF]) and C. duriuscula (associated with AMF). Moreover, the foliar δ 15 N of all three species increased with increasing N addition rates, with a sharp increase above an N addition rate of ~10 g N m −2 year −1 . Foliar δ 15 N values were significantly higher when NH 4 HCO 3 and urea were added than when NH 4 NO 3 was added, suggesting that adding weakly acidifying N compounds could result in a more open N cycle. Overall, our results imply that assessing the N transformation processes in the context of increasing global N deposition necessitates the consideration of N deposition rates, forms of the deposited N compounds, and N utilization strategies of the co‐existing plant species in the ecosystem.